Establishing and prioritizing research questions for the prevention, diagnosis and treatment of hair loss (excluding alopecia areata): the Hair Loss Priority Setting Partnership. (16th January 2018) - Macbeth, A.; Tomlinson, J.; Messenger, A.; Moore‐Millar, K.; Michaelides, C.; Shipman, A.; Kassim, J.; Brockley, J.; Szczecinska, W.; Farrant, P.; Robinson, R.; Rodgers, J.; et al.
Summary: Background : Hair and scalp problems are common. Unfortunately, many uncertainties exist around the most effective management and treatment strategies for these disorders. Objectives : To identify uncertainties in hair‐loss management, prevention, diagnosis and treatment that are important to both people with hair loss and healthcare professionals. Methods : A Hair Loss Priority Setting Partnership was established between patients, their carers and relatives, and healthcare professionals to identify the most important uncertainties in hair loss. The methodology of the James Lind Alliance was followed to ensure a balanced, inclusive and transparent process. Results : In total, 2747 treatment uncertainties were submitted by 912 participants; following exclusions 884 uncertainties relating to hair loss (excluding alopecia areata) were analysed. Questions were combined into 'indicative uncertainties' following a structured format. A series of ranking exercises further reduced this list to a top 25 that was taken to a final prioritization workshop where the top 10 priorities were agreed. Conclusions : We present the top 10 research priorities for hair loss (excluding alopecia areata) to guide researchers and funding bodies to support studies important to both patients and clinicians. Abstract : What's already known about this topic? Many uncertainties exist around the management and treatment of hair loss. What does this study add? We present the top 10 uncertainties in hair‐loss management, prevention, diagnosis and treatment that are important to patients, their carers and healthcare professionals. These prioritized research uncertainties can be used to guide researchers and funding bodies when deciding to invest in hair‐loss research studies. Linked Comment: Holmes. Br J Dermatol 2018;178 :330–331 . Plain language summary available online